The influence of Sunday school teaching curriculum based on 2 Timothy 3:15-17 - Wahyuni, Sri (Technium Social Sciences Journal, 2022)
The congregation has not taken responsibility for carrying out the functions and duties of the church where the congregation is less aware of the obligation as believers to serve together in advancing the church. Just as a congregation that has accepted Christ as Lord and Savior gave itself to be used by God. God calls someone to serve not those who want to be served, equipping themselves through various ways including learning more about theology formally in theological colleges. You can also take part in various opportunities to take part in training organized by official institutions on available opportunities. Opportunity to build self and knowledge in Sunday school ministry so that it will become a servant who has good quality. This research involves the congregation in responding to God’ s call as a teacher who is responsible to Christ and during service. Church growth is always marked by the growth of the congregation spiritually building. One of the characteristics of a growing church is that the congregation is involved in the ministry together to build the body of Christ and serve one another in the love of Christ. But the call as believers as members of the body of Christ who serve fellow members becomes very absolute in the Christian community. The five functions of the church in understanding the Baptists that occurred were: Koinonia, Diakonia, Marturia, Discipleship, and Worship. motivated to write a scientific paper “The Influence of Sunday School Teaching Curriculum Based on 2 Timothy 3:15-17.